27 Shotgun proteomics reveal seminal plasma proteomes are reflective of boar reproductive performance. (30th November 2020) - Mills, Kayla M; Aryal, Uma; Sobreira, Tiago; Minton, Amanda; Casey, Theresa; Stewart, Kara R
Abstract: Subfertile boars have a negative economic impact for producers and need to be identified before they enter the breeding herd. Current semen evaluation techniques are not able to identify all subfertile boars. Seminal plasma proteins are essential for normal sperm function and transport and play an important role in fertilization. We hypothesize that seminal plasma proteins affect fertility, and thus differences in protein profiles reflect differences in boar fertility. The objective of this study was to use LC-MS/MS for shotgun proteome analysis to investigate whether differences in boar fertility phenotype can be differentiated by seminal plasma protein expression. Following 50 single-sire matings, boars were categorized into one of four phenotypes: high farrowing rate and high total born (HFHB; n=9), high farrowing rate with low total born (HFLB; n=10), low farrowing rate and low total born (LFLB; n=9), and low farrowing rate with high total born (LFHB; n=4). There were 436 proteins measured in at least one sample across all animals. There were 245 high confidence proteins and 56 were differentially abundant (P < 0.05) between the high fertility phenotype (HFHB) and at least one of the three subfertile groups. Proteins associated with fertility and free radical detoxification were more abundant in HFHB whereas subfertile phenotypes had a greater abundance of blood microparticle proteins, biomarkers of inflammation, and IMPA1, which regulates inositol production. Findings support that seminal plasma protein profiles are distinct between boars with different fertility phenotypes and have the potential to predict boar reproductive performance.